2012
DOI: 10.1093/icvts/ivs088
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of a pulmonary artery aneurysm due to a regurgitant quadricuspid pulmonary valve

Abstract: We report the case of a patient with a pulmonary artery (PA) aneurysm secondary to a regurgitant quadricuspid pulmonary valve, in which both lesions were successfully repaired. The patient, a 16-year old boy, was known to have had pulmonary regurgitation and progressive dilation of the PA for years. He was operated on when he developed symptoms of effort, a dilated right ventricle and a PA of 55 mm. The quadricuspid pulmonary valve was an intraoperative finding. It had a dilated annulus, two normal cusps, a th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…6 Many patients with PAA also present with pulmonary valve regurgitation, and even though it is more plausible that it is a consequence of annulus dilatation by the PAA, it may also be an independent etiologic factor in the formation of a PAA. 3,10 Patients with the congenital malformation of an absent pulmonary valve syndrome represent a PAA subset that might link pulmonary valve regurgitation to PAA formation ( Figure 1). Absent pulmonary valve syndrome has been described as a rare variant of tetralogy of Fallot but has also been associated with ventricular septal defects and Uhl anomaly and very seldom occurs as an isolated congenital heart defect.…”
Section: Congenital Causesmentioning
confidence: 99%
See 4 more Smart Citations
“…6 Many patients with PAA also present with pulmonary valve regurgitation, and even though it is more plausible that it is a consequence of annulus dilatation by the PAA, it may also be an independent etiologic factor in the formation of a PAA. 3,10 Patients with the congenital malformation of an absent pulmonary valve syndrome represent a PAA subset that might link pulmonary valve regurgitation to PAA formation ( Figure 1). Absent pulmonary valve syndrome has been described as a rare variant of tetralogy of Fallot but has also been associated with ventricular septal defects and Uhl anomaly and very seldom occurs as an isolated congenital heart defect.…”
Section: Congenital Causesmentioning
confidence: 99%
“…19 However, some authors have suggested that the Hughes-Stovin syndrome is a cardiovascular manifestation of the Behçet syndrome and therefore part of the same disease process. 18,19 PA hypertension (PAH) is an important cause of PAA formation 10,14,20 and has been suggested to be a clinical symptom of an existing PAA. 21 PAH is a clinical syndrome characterized by an increase in pulmonary vascular resistance leading to failure of the right side of the heart and ultimately to death.…”
Section: Acquired Causesmentioning
confidence: 99%
See 3 more Smart Citations